Disease, invasions and conservation: no evidence of squirrelpox virus in grey squirrels introduced to Italy. (17th July 2018) - Romeo, C.; McInnes, C. J.; Dale, T. D.; Shuttleworth, C.; Bertolino, S.; Wauters, L. A.; Ferrari, N.
Abstract: Native red squirrels Sciurus vulgaris in Great Britain and Ireland are threatened by alien grey squirrels S. carolinensis through exploitation competition and spillover of squirrelpox virus (SQPV). By accelerating the replacement of red squirrels by the invader, SQPV represents a fundamental factor to consider when planning management and conservation strategies. In mainland Europe, grey squirrels introduced to Italy threaten the survival of the whole continental red squirrel population, but no extensive surveys for SQPV presence have been carried out in the region. We therefore investigated SQPV infection in north Italian grey squirrel populations through a combination of serological and molecular methods. Firstly, we analysed sera from 285 individuals through an enzyme‐linked immunosorbent assay (ELISA) to detect antibodies against SQPV. Secondly, a PCR designed to amplify a segment of the G8R SQPV gene was carried out on DNA extracted from swabs and skin tissue samples from a second set of 66 grey squirrels. ELISA tests identified four reactors (1.4%), but the subsequent PCR survey did not detect any SQPV DNA. Based on the low prevalence observed and on PCR results, we believe that the four suspected positives were the result of an ELISA cross‐reaction following exposure to another pox virus. Considering sample size and performances of the two methods, confidence of freedom from SQPV resulted above 99.9%. However, because of the severe impact of SQPV on red squirrels, we recommend the implementation of a passive surveillance plan for the early detection of an SQPV emergence in continental Europe. Abstract : Squirrelpox virus transmitted by alien grey squirrels played a crucial role in the decline of native red squirrels in Great Britain and Ireland. It is still unknown whether the virus is circulating in Italy too, where it could potentially threaten the whole European red squirrel population. We extensively surveyed grey squirrels introduced to Italy for squirrelpox virus infection through a combination of serological and molecular methods, but did not find any evidence of the disease in the area. We discuss the implications of this absence and recommend the activation of passive surveillance plans to avoid any disease emergence that could threaten native squirrels survival. Photo credit: Sandro Bertolino.